2010
DOI: 10.3109/00016349.2010.484044
|View full text |Cite
|
Sign up to set email alerts
|

High cesarean prevalence in a national population‐based study in Brazil: the role of private practice

Abstract: CS rates are generally very high in Brazil. They are significantly higher than the average among women attending private/insured antenatal care, among the highly educated, and in provinces with higher socioeconomic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
1
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 29 publications
8
93
1
10
Order By: Relevance
“…Regarding educational level, the highest percentage (28%) of the study sample graduated from Primary school as shown in table (1), the higher level of education was associated with preference for C-section (10).women with low level of education had no knowledge of ceaserean section, like wise women with highest level of education (p<o.oo) had the highest level of knowledge about cesarean section (11). In another study, in Brazil it was concluded that the highly educated women had a significantly higher preference for C-section and also experienced a higher rate of C-section (12). Regarding Occupation, the highest percentage (82%) of the study sample were housewives as table (1).…”
Section: Dscussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Regarding educational level, the highest percentage (28%) of the study sample graduated from Primary school as shown in table (1), the higher level of education was associated with preference for C-section (10).women with low level of education had no knowledge of ceaserean section, like wise women with highest level of education (p<o.oo) had the highest level of knowledge about cesarean section (11). In another study, in Brazil it was concluded that the highly educated women had a significantly higher preference for C-section and also experienced a higher rate of C-section (12). Regarding Occupation, the highest percentage (82%) of the study sample were housewives as table (1).…”
Section: Dscussionmentioning
confidence: 82%
“…The women with cesarean section request rate was higher among with housewives. 12 The result of the study shows that the highest percentage (50 %) of sample has (2-3) pregnancies as shown in table (2). Around 70% of (156) women were in their second pregnancy preferred cesarean section (13) .…”
Section: Dscussionmentioning
confidence: 85%
“…Serbia is recording the increase of incidence of Caesarean sections. In the period from 1991 to 2000 in Serbia, the incidence grows from 9.13% to 15.3% [2]. due to complications in pregnancy of low gestation and threatening or initiated preterm delivery are directed to the tertiary level health care institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable growth rate of Cesarean sections is noticed in Latin America, where no country has a lower incidence than 23%, and in Chile even 40% of deliveries are completed surgically. Brazil records a very high percentage of Caesarean sections 43.6%, and in private clinics it even amounts to 88.2% [2]. On the other hand, in the WHO bulletin for the year 2008, the high level of maternal mortality can be noticed, with over 500 maternal deaths per 100 000 births, which is associated with low rate of Caesarean sections to 5% [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative safety of cesarean sections and changing patient expectations contributed to a further rise in CDs. Obstetricians working privately discovered that planned CDs took up much less of their time, leading to greater profits, and in countries with a large private sector like Brazil, CDs are performed at present in about 70% of women, with ‘only' 25% in general hospitals [3]. It is regularly quoted that women want a CD, but in my opinion it has been mainly the doctors who have promoted the elective CD, and, as a consequence, women started to ask for it.…”
Section: Why Do Cesarean Deliveries Continue To Rise?mentioning
confidence: 99%